VIRTUAL AND AUGMENTED REALITY TECHNOLOGIES - Makhmudov Mukhtorjon Abdumalik o’g’li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the essence of virtual and augmented reality technologies. Augmented reality (AR) augmented reality (AR) technologies as sensory devices that help to fill in and receive information about an object. VR (virtual reality, VR, artificial reality) Virtual reality is a way to create information about an object using technical means, to convey it to people through their imagination. Opinions and comments are provided on the challenges of AR / VR technology development and the characteristics of the global market.